Igraszki z konwencjami - postscriptum o kobiecości do kilku znanych utworów brytyjskich z XIX wieku = Playing with conventions. Several remarks on femininity in a few notable 19th century british novels - Wiatrzyk-Iwaniec, Marta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Both, the gothic novel and the suspense novel use symbols, themes, motifs and patterns that can beeasily identified and decoded. Nevertheless, Mary Elizabeth Braddon ("Lady Audley?s Secret"), WilkieCollins ("The Woman in White"), Jane Austen ("Northanger Abbey") and Eaton Stannard Barrett ("TheHeroine") show that it is possible to play with patterns even within the frame of a conventionalizednovel.
Keywords: literatura angielska; powieść kryminalna; 19 w.